2009
DOI: 10.1080/09537320902969133
|View full text |Cite
|
Sign up to set email alerts
|

Critical factors for success in university–industry research projects

Abstract: This study provides insight into the reality of university-industry technology transfer through the assessment of some of the most influential factors for success or failure in research contracts. This widespread mechanism of technology transfer is examined in the light of exhaustive information and experience gathered from thirty interviews with qualified university researchers. The interviewees, who have been directly involved in collaborative projects with industry partners, have deeply described both sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 31 publications
3
43
0
4
Order By: Relevance
“…Although the extensive discussion of UILs in academic literature and government reports has established several UIL success factors (Barbolla and Corredera, 2009;Thune, 2011), it remains unclear whether the drivers are the same or differ throughout the relationship. Therefore, we focus on relational characteristics that reflect the interpersonal linkages between actors, which represent the actor layer of the A-R-A model (Håkansson and Johanson, 1992).…”
Section: Drivers Of University-industry Relationship Successmentioning
confidence: 99%
“…Although the extensive discussion of UILs in academic literature and government reports has established several UIL success factors (Barbolla and Corredera, 2009;Thune, 2011), it remains unclear whether the drivers are the same or differ throughout the relationship. Therefore, we focus on relational characteristics that reflect the interpersonal linkages between actors, which represent the actor layer of the A-R-A model (Håkansson and Johanson, 1992).…”
Section: Drivers Of University-industry Relationship Successmentioning
confidence: 99%
“…The analytical technique used focused on drafting an explanation of the case to generate a significant theoretical contribution. This analytical perspective was selected because, although U-I collaborations are difficult and filled with paradoxes and challenges, great achievements have been realized as a result of such cooperation (Barbolla and Corredera, 2009). In the event that answers to the initial research questions would lead us toward other factors, we attempted to draft a new analysis directed toward our rival research explanations (Proposals 1 and 2), as mentioned above.…”
Section: Methodsology and Data Collectionmentioning
confidence: 99%
“…The current complexity of problems and the need for multidisciplinary approaches require an interaction of ideas and an exchange of knowledge. The exchange of information between universities and industries is bi-directional (Barbolla and Corredera, 2009;Lai, 2011). Industry problems and market needs are fundamental to research objectives in the university environment.…”
Section: University-industry Collaborationmentioning
confidence: 99%
“…Nieto et al [34] examined the theoretical foundation of the S-curve model and discuss problems experienced with its implementation, particularly the measurement of performance indicators. Barbolla and Corredera [35] found that satisfactory technology transfer is a combination of factors that include real interest in the stakeholder organisations in both project development and in its final result, as well as high motivation and a good command of the necessary knowledge to undertake the project.…”
Section: Stakeholders and Technology Transfermentioning
confidence: 99%